(untitled) (The Pretoria Student Law Review, 2021)
This essay deals with the ‘advantage to creditors’ requirement imposed by the Insolvency Act, in South African law. This essay is divided into four parts. Firstly, the requirement will be examined in order to establish the objective it aims to achieve. It will then go on to describe the various ways in which the requirement is implemented during the sequestration process in order to achieve this objective. The second part will discuss how courts interpret the relevant provisions with reference to case law. In the third part, South African insolvency law will briefly be compared to foreign insolvency law in order to raise some potential concerns about the emphasis on the ‘advantage to creditors’ requirement in our law. Finally, with due regard to the current legal institutions and proposals for legal reform in South Africa, conclusions will be drawn as to the necessity of revisiting the scope and implementation of this requirement.